4-Aminoindoles as 1, 4-bisnucleophiles for diversity-oriented synthesis of tricyclic indoles bearing 3, 4-fused seven-membered rings. Issue 24 (5th June 2019) - Chen, Shaomin; Ravichandiran, Palanisamy; El-Harairy, Ahmed; Queneau, Yves; Li, Minghao; Gu, Yanlong
Abstract : A straightforward access to tricyclic indoles bearing 3, 4-fused seven-membered rings was established by using 4-aminoindoles as 1, 4-bisnucleophiles in three-component reactions. Abstract : A straightforward access to tricyclic indoles bearing 3, 4-fused seven-membered rings has been established by using 4-aminoindoles as 1, 4-bisnucleophiles in three-component reactions. 1 H -Azepino[4, 3, 2- cd ]indoles, 4, 6-dihydro-1 H -azepino[4, 3, 2- cd ]indoles and 1, 3, 4, 6-tetrahydro-5 H -azepino[4, 3, 2- cd ]indol-5-ones could thus be synthesized in one pot in moderate to good yields. Beyond opening access to 3, 4-fused tricyclic indoles, the use of easily accessible 4-aminoindoles as C, N-1, 4-bisnucleophiles also provides a new platform to be used in a diversity-oriented synthesis strategy, fully displaying its benefits of maximizing molecular complexity and reaction diversity.